2014
DOI: 10.1002/chem.201304484
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Growth of ZnO Nanocrystals on Mixed Metal Oxide Surfaces

Abstract: An in situ method for the growth of ZnO nanocrystals on Zn/Al mixed metal oxide (MMO) surfaces is presented. The key to this method is the thermal treatment of Zn/Al layered double hydroxides (Zn/Al LDHs) in the presence of nitrate anions, which results in partial demixing of the LDH/MMO structure and the subsequent crystallization of ZnO crystals on the surface of the forming MMO layers. In a first experimental series, thermal treatment of Zn/Al LDHs with different fractions of nitrate and carbonate in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A simple route to engineer surface texture is the growth of oxides on metal substrates. Thermal treatment of metal substrates provides a straightforward and tunable method to grow oxides. Nonetheless, the inherently high stiffness and differences in thermal expansivities pose significant challenges in surface modification. Liquid metals, however, provide an alternative because they form nanoscale oxide shells that, because of size effects, are compliant to stresses. , Eutectic gallium–indium (EGaIn: 75.5% Ga, 24.5% In w/w; mp ≈ 15.7 °C) has recently found applications in soft and stretchable electronics, ,, functional microparticles, ,,, molecular electronics, and functional devices. , EGaIn bears a thin (∼0.7–3 nm) passivating film of predominantly Ga 2 O 3 on the surface, rendering the liquid metal non-Newtonian as described above. ,,,,, The EGaIn passivating oxide layer has a graded oxide structure with the surface being primarily Ga 2 O 3 , with underlying layer(s) of Ga and In suboxides, beneath which segregated In metal has been observed. ,− This complex structure spontaneously forms to a thickness of ca.…”
Section: Introductionmentioning
confidence: 99%
“…A simple route to engineer surface texture is the growth of oxides on metal substrates. Thermal treatment of metal substrates provides a straightforward and tunable method to grow oxides. Nonetheless, the inherently high stiffness and differences in thermal expansivities pose significant challenges in surface modification. Liquid metals, however, provide an alternative because they form nanoscale oxide shells that, because of size effects, are compliant to stresses. , Eutectic gallium–indium (EGaIn: 75.5% Ga, 24.5% In w/w; mp ≈ 15.7 °C) has recently found applications in soft and stretchable electronics, ,, functional microparticles, ,,, molecular electronics, and functional devices. , EGaIn bears a thin (∼0.7–3 nm) passivating film of predominantly Ga 2 O 3 on the surface, rendering the liquid metal non-Newtonian as described above. ,,,,, The EGaIn passivating oxide layer has a graded oxide structure with the surface being primarily Ga 2 O 3 , with underlying layer(s) of Ga and In suboxides, beneath which segregated In metal has been observed. ,− This complex structure spontaneously forms to a thickness of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of LDHs containing Zn, Ni, Fe and Cr with carbonate as the interlayer anion showed that the decomposition stages found for the Mg/Al system are also valid for other metal combinations, while the deviance of the respective temperature ranges amounts to 50 to 100 °C for some LDH species. 194,197,198 Also the type of interlayer anion has an effect on the structural transformation of LDHs upon thermal treatment, which was shown for Zn/Al LDHs containing different interlayer anions. 198,199 Furthermore, it is noteworthy that many LDH variants exhibit the special feature called the "memory effect", i.e.…”
Section: Thermal Stability Of Ldhs and Conversion Into Mixed Metal Ox...mentioning
confidence: 89%
“…194,197,198 Also the type of interlayer anion has an effect on the structural transformation of LDHs upon thermal treatment, which was shown for Zn/Al LDHs containing different interlayer anions. 198,199 Furthermore, it is noteworthy that many LDH variants exhibit the special feature called the "memory effect", i.e. after thermal treatment up to a certain temperature (usually 200 to 500 °C) it is possible to re-establish the LDH structure through exposure to water steam or aqueous solutions of certain lost or desired interlayer anions.…”
Section: Thermal Stability Of Ldhs and Conversion Into Mixed Metal Ox...mentioning
confidence: 89%
“…Although multiple methods are available to grow oxides, thermal treatment is still a straightforward and effective method to achieve the same. 65,66,68,137,138 Thermal oxidation not only provides characteristic texture but also renders texture tunability by varying temperature.…”
Section: Current Research On Liquid Metals and Alloysmentioning
confidence: 99%